Penguatan Kemampuan Techological Pedagogical Content Knoweledge (TPACK) dan Cultural Literacy Guru PAI Melalui Pelatihan Pembelajaran Berbasis Multicultural Education - Sari, Herlini Puspika; Ilhami, Aldeva (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
The purpose of this community service is to improve the TPACK skills and cultural literacy of educators through a multicultural-based Islamic religious learning (PAI) workshop. The community service method uses participatory action research (PAR). The PAR cycle includes 4 stages for each cycle, namely planning (Plan action), action (Take Action), observation (observe), and reflection (Reflection).Mentoring is carried out for PAI group teachers which is carried out at MA Cendekia Bangsa Pekanbaru. The implementation of activities includes strengthening insights into multicultural-based PAI learning, strengthening knowledge of local Riau Malay wisdom, and preparing learning scenarios. Teachers apply learning in the classroom according to the scenarios that have been studied. There is an increase in the TPACK skills and cultural literacy of PAI teachers after participating in a multicultural education-based PAI learning workshop. There was a positive response from teachers after participating in the workshopwhich was indicated by satisfaction and follow-up plans to be carried out.